Kvalitet i journalistik - Svith, Flemming (Journalistica, 2006)
This article argues that the quality criteria of the press have lost their relevance for reliable journalism. This happens as the press shift its focus from being “first with the last” to “explanation of what happened”. The quality criteria were developed during a time, when the mass medias were the only source of news to the public. Journalism was selecting, sorting and presentation of facts. Quality was speed and precision. Internet has broken the monopoly of the press on news supply, and the press focus on analysing and interpretations with the purpose of uncover connections, consequences or solutions, which not can be seen. In that way journalism is used on domains, which is dominated by science. New quality criteria of the press can be developed with inspiration from the criteria of science.